Development of a systems model to visualise the complexity of children's independent mobility. Issue 1 (2nd January 2016) - Badland, Hannah; Kearns, Robin; Carroll, Penelope; Oliver, Melody; Mavoa, Suzanne; Donovan, Phil; Parker, Karl; Chaudhury, Moushumi; Lin, En-Yi; Witten, Karen
Abstract : Substantial changes to the built environment, urbanisation patterns, and societal norms have contributed to limiting children's opportunities for being independently mobile. Several linear causal pathway models have been developed to understand the influences on children's independent mobility; however feedback loops between and within the various levels of influence cannot be modelled using such an approach. The purpose of this paper is to refine the interrelationships of factors related to children's independent mobility, taking into account earlier models, broader contextual factors, recent children's geographies literature, and feedback loops. Systems model components were informed by attributes known to influence children's independent mobility, related qualitative findings, and the development of a framework that could lend itself to multilevel modelling approaches. This systems model may provide a useful structure for identifying how best to develop and monitor interventions to halt the declining rates of children's independent mobility.